Agricultural R&D in Togo: An Assessment of the Togolese Agricultural Research Institute - Adabe, Kokou Edoh; Stads, Gert-Jan (International Food Policy Research Institute, 2014)
The Agricultural Science and Technology Indicators (ASTI) initiative of the International Food Policy Research Institute (IFPRI) and the West African Council for Agricultural Research and Development (CORAF/WECARD) conducted an in-depth study of critical issues relating to human, financial, and institutional agricultural R&D capacities in Burkina Faso and five other West African countries (Benin, Ghana, Senegal, Sierra Leone, and Togo). As part of this study, detailed quantitative and qualitative data were collected at an institutional level. This included a staff motivation survey targeting a representative group of research and managerial staff in terms of position, qualification, gender, seniority, and physical location.